Identification of cow’s and buffalo’s milk and dairy product using a DNA-based method - Soltész, Beáta; Gulyás, Gabriella; Csikós, Ádám; Koncsos, Gábor; Vass, Nóra; Oláh, János; Jávor, András; Czeglédi, Levente (Acta Agraria Debreceniensis, 2012)
Aim of our study was the optimization of a DNA method, that is appropriate for reliable, low cost identification of animal species in milk and dairy product (cheese) and to determine the ratio of species. Mitochondrial DNA was used in our work to analyse buffalo/cow milk mixtures contained different ratio of bovine milk such as 0.1%, 0.5%, 1%, 1.5%, 2%, 5%, 10%, 15% (v/v%). Buffalo cheese were produced using buffalo and cows milk (0%, 2%, 5%, 10%, 15% – v/v% cows milk in buffalo milk). In case of milk mixtures, using species specific primers, the PCR assay showed a 0.5 v/v% detection limit. Cattle, in the buffalo/cows milk 99.9/0.1 v/v% mixture, was not detectable. The identification of buffalo and cows DNA in cheese was successful. The intensity of eletroforetic PCR fragment indicated the increase of cow milk ratio in milk and cheese samples as well.